The myopathy-causing mutation DNM2-S619L leads to defective tubulation in vitro and in developing zebrafish - Elizabeth M. Gibbs; Ann E. Davidson; William R. Telfer; Eva L. Feldman; James J. Dowling (The Company of Biologists, 2014)
DNM2 is a ubiquitously expressed GTPase that regulates multiple subcellular processes. Mutations in DNM2 are a common cause of centronuclear myopathy, a severe disorder characterized by altered skeletal muscle structure and function. The precise mechanisms underlying disease-associated DNM2 mutations are unresolved. We examined the common DNM2-S619L mutation using both in vitro and in vivo approaches. Expression of DNM2-S619L in zebrafish led to the accumulation of aberrant vesicular structures and to defective excitation-contraction coupling. Expression of DNM2-S619L in COS7 cells resulted in defective BIN1-dependent tubule formation. These data suggest that DNM2-S619L causes disease, in part, by interfering with membrane tubulation.